EFFECTIVENESS OF THE EXPERIENTIAL LEARNING MODEL IN IMPROVING SELF-ESTEEM IN VOCATIONAL HIGH SCHOOL STUDENTS - Taufik Sani; Ahmad Jawandi (SOSIOEDUKASI, 2025)
Self-esteem is one of the psychological aspects that plays an important role in the development of students, especially in Vocational High Schools (SMK), which require their readiness to face the world of work. However, many students in SMK experience low levels of self-esteem, which has an impact on self-confidence, learning motivation, and the ability to adapt to social and academic environments. This study aims to analyze the effectiveness of the Experiential Learning model in improving self-esteem of students in SMK. This study uses an experimental method with a pretest-posttest control group design. The research sample consisted of SMK students who were divided into an experimental group that received learning with the Experiential Learning model and a control group that used conventional learning methods. The data analysis technique was carried out using statistical tests to see the difference in self-esteem before and after the intervention. Based on the data analysis carried out, the results showed that the Experiential Learning model had a positive effect on improving self-esteem of students in SMK. This is evidenced by the average obtained that the mean pretest score of the experimental group was 8.95 and the control group was 90.70. Furthermore, the posttest results of the experimental group were 103.20 and the control group was 90.50. Based on the average pretest and posttest results, it can be concluded that the experimental group given the Experiential Learning model treatment had an increase in scores, while the control group that was not given treatment did not experience a significant increase.